Trace elements and isotopes analyses on historical samples of white sharks from the Mediterranean Sea. Issue 1 (1st January 2021) - Bevacqua, L.; Reinero, F. R.; Becerril-García, E. E.; Elorriaga-Verplancken, F. R.; Juaristi-Videgaray, D.; Micarelli, P.; Galván-Magaña, F.; Curiel-Godoy, P.; Giglio, G.; Tripepi, S.; Barca, D.; Sperone, E.
Abstract: The white shark Carcharodon carcharias has been present in the Mediterranean Sea since 3.2 million years ago. Nevertheless, the current population shows a low genetic variability suggesting an endangered small population, on which there is scarce information regarding ecotoxicology or trophic ecology. Given that white shark's sightings are rare in the Mediterranean and the possibility of obtaining samples is highly limited, the aim of this research was to provide general information regarding the concentration of trace elements and stable isotopes (δ 15 N and δ 13 C). Laboratory analyses were performed on 18 and 12 subsamples from two different white sharks' vertebrae obtained from two adult specimens caught in 1987, in Favignana Island, Italy. Perforations were made along the vertebrae to describe both trace elements and stable isotopes at different life stages. A total of 38 trace elements were analysed, in which the highest concentrations were found in Fe, Sr, U, Pb, and Zn. The fluctuations of these elements during the ontogeny of both individuals could have been related to changes in diet and environment, although the specific origin remains unknown. Regarding stable isotopes, the vertebrae from the male showed an isotopic range from 9.6‰ to 10.8‰ (δ 15 N) and from −16.5‰ to −13.0‰ (δ 13 C) with a mean ± SD value of 10.3 ± 0.4‰ for δ 15 N and −14.6 ± 1.3‰ for δ 13 C; whereas the female vertebrae had an isotopic range from 9.8‰ to 11.1‰ (δ 15 N) and from −16.9‰ to −15.0‰ (δ 13 C), with a mean ± SD value of 10.8 ± 0.6‰ for δ 15 N and −15.8 ± 0.8‰ for δ 13 C. There were no significant δ 15 N differences (U = 6, p = 0.07346) between the two individuals. However, there were just significant differences in δ 13 C (t = −1.8, p = 0.049256), which could suggest sexual segregation in terms of habitat use and feeding habits.